PENERAPAN MODEL WATERFALL PADA APLIKASI BANK SAMPAH - Rofiq, Nur; Perdananto, Agung; Jaya, Nur (ISTEK WIDURI, 2021)
The Waterfall Model is also very widely used by organizations and is developed with certain software whose results can overcome changes and weaknesses. This research is designed to manage the data of 'Jawara' customers because currently, they are still using a semi-computerized method that only writes them down in a book list. This study uses a qualitative approach with descriptive analysis with stages, namely system engineering, analysis, design, code generation, and the Waste Bank application testing. The application of the waterfall model in the Waste Bank information system application is a solution in the use of previously still recording customer waste deposits in Excel files, making quick and detailed waste price list reports, simplifying customer data processing, accelerating the search for required information and making it easier for customers to view a history of withdrawal and deposit transactions that previously still used semi-computerized methods. The result of this research is an application that has been made into a solution in making quick and detailed waste price list reports, simplifying customer data processing and speeding up information search, viewing withdrawal and deposit transaction history.